(untitled) (Journal Of Educational and Psychological Researches, 2023)
This study aims to identify the degree of Arabic language teachers at the secondary stage possessing the teaching competencies necessary to develop the skills of literary savor among their students from the perception of educational leaders in Bisha Province. To achieve the objectives of the study, the descriptive approach was used by adopting a comprehensive survey method. The study sample consisted of (48) school principals and Arabic language supervisors in Bisha Province who supervise the teaching of Arabic language at the secondary level in Bisha Province. The necessary data was collected using a questionnaire. The results of the study revealed that the evaluation of the study sample for the degree to which Arabic language teachers at the secondary stage possess the teaching competencies necessary to develop literary appreciation skills among their students was medium. In light of this result, the study recommended holding training courses for male and female teachers to raise the level of availability of the teaching competencies necessary to develop their literary savour skills, to encourage them to apply these competencies in the reality of teaching Arabic literature classes and to evaluate their performance